Staff and offender perspectives of Integrated Offender Management and the impact of its introduction on arrests and risk of reoffending in one police force region - Sleath, Emma (Policing and society, 2019)
The Integrated Offender Management (IOM) framework was introduced in England and Wales in 2009. The aims of the research outlined in this paper were to examine the impact of the introduction of an IOM approach in one large police force region and the perceptions of it by offenders and staff. There were two parts to the study. The first involved the use of a within-participant approach to establish whether IOM supervision reduced the level of arrests and risk of reoffending in a sample of offenders. The second involved interviewing offenders and staff involved in IOM regarding their perceptions of it with a focus on effectiveness. The findings showed that the level of arrests (medium effect) and the risk of reoffending (large effect) reduced in the 18 months following the introduction of IOM in comparison to the 18 months prior to the introduction of IOM. Six superordinate themes were identified from staff and offender interviews that highlighted the core elements of IOM, the effectiveness of IOM in reducing offending, how reoffending is reduced, communication, the offender manager role, and the challenges of IOM. The findings offer tentative support for the effectiveness of IOM provision in this geographic region in reducing offending and in identifying factors that staff and offenders believe contribute to the effectiveness of this approach and can improve future IOM provision.